2001
DOI: 10.1359/jbmr.2001.16.7.1329
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover and Density in Obese Premenopausal Women During Moderate Weight Loss and Calcium Supplementation

Abstract: Bone turnover is increased during weight loss in postmenopausal women and can be suppressed with calcium supplementation. In this study, we assessed the influence of energy restriction with and without calcium supplementation (1 g/day) in premenopausal women. Thirty-eight obese premenopausal women (body mass index [BMI] of 35.0 ؎ 3.9 kg/m 2 ) completed a 6-month study of either moderate weight loss or weight maintenance. During weight loss, women were randomly assigned to either a calcium supplementation (n ‫؍… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
4
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 37 publications
7
79
4
3
Order By: Relevance
“…It may be that Ca intake cannot suppress the high rate of bone turnover associated with severe caloric restriction. Other high bone turnover conditions, such as pregnancy and lactation, show either a beneficial effect of Ca supplementation to reduce mobilization of skeletal mineral stores (Reid et al, 1993;Prince et al, 1995;Cepollaro et al, 1996;Ricci et al, 1998;Shapses et al, 2001) and BPb levels (Hernandez-Avila et al, 2003;Ettinger et al, 2006) or no effect on BPb levels (Hertz-Picciotto et al, 2000;Gulson et al, 2004Gulson et al, , 2006. We found a weak association amongst all women between higher Ca intakes and lower bone resorption (PYD cross-links) and BPb levels during caloric restriction.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It may be that Ca intake cannot suppress the high rate of bone turnover associated with severe caloric restriction. Other high bone turnover conditions, such as pregnancy and lactation, show either a beneficial effect of Ca supplementation to reduce mobilization of skeletal mineral stores (Reid et al, 1993;Prince et al, 1995;Cepollaro et al, 1996;Ricci et al, 1998;Shapses et al, 2001) and BPb levels (Hernandez-Avila et al, 2003;Ettinger et al, 2006) or no effect on BPb levels (Hertz-Picciotto et al, 2000;Gulson et al, 2004Gulson et al, , 2006. We found a weak association amongst all women between higher Ca intakes and lower bone resorption (PYD cross-links) and BPb levels during caloric restriction.…”
Section: Discussionmentioning
confidence: 56%
“…Hence, it is possible that increased Ca intake had a marginal effect on attenuating BPb during severe weight loss, especially if intake was deficient prior to surgery (i.e., single patient example in Figure 3). This is of particular importance because caloric restriction results in Ca intake that is often in the deficient range (Ricci et al, 1998;Shapses et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of weight loss on bone mineral remains controversial. Although weight loss in postmenopausal women apparently results in loss of bone mass (Avenell et al, 1994;Ricci et al, 1998Ricci et al, , 2001Riedt et al, 2005;, findings in premenopausal women (Salamone et al, 1999;Fogelholm et al, 2001;Shapses et al, 2001;Park et al, 2007;Riedt et al, 2007) and in middle-aged men (Pritchard et al, 1996; are inconsistent. The discrepant results may be explained, in part, by differences in skeletal site examined, baseline body weight, rate or magnitude of weight loss, calcium or protein intake, physical activity and duration of post-weight loss follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in overweight pre-and post-menopausal women have demonstrated that high calcium intakes (1.5-1.8 g/day) both prevent the reduction in bone mass associated with moderate weight loss, and suppress bone turnover and parathyroid hormone (PTH) secretion (Ricci et al, 1998;Jensen et al, 2001;Shapses et al, 2001). Weight-loss diets that are high in dairy and, therefore, in calcium, vitamin D and protein content also have been shown to preserve BMD and suppress bone turnover after weight reduction (Bowen et al, 2004;Thorpe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9,31 Some studies suggest that supplementation of this mineral in women perimenopause reduces negative alterations in BMD during weight modifications. 32,33 Although the studies are inconclusive. and women, respectively.…”
Section: Further Hypotheses Involved In the Alterations Of Bmc And Bmdmentioning
confidence: 99%